School Counsellors’ Understanding of Non-Suicidal Self-Injury: Experiences and International Variability - Duggan, Jamie M.; Heath, Nancy L.; Toste, Jessica R.; Ross, Shana (Canadian Journal of Counselling and Psychotherapy, 2011)
Non-suicidal self-injury (NSSI) is a concern among professionals working with youth. The present study examined school counsellors’ experiences, training and school preparedness, perceived knowledge, beliefs, and intervention approaches related to NSSI. Participants were 470 school counsellors (417 female, 53 male) from across North America (156 Canada, 314 United States). Although NSSI is largely within counsellors’ scope of practice, as evidenced by the 92% who reported working with a student who engaged in NSSI at some point during their career, counsellors reported only moderate levels of NSSI knowledge, a lack of formal training, and an absence of school policies concerning NSSI management. American counsellors endorsed more media-based representations about NSSI than their Canadian counterparts. Discussion focuses on the need for training among school counsellors and the improvement of service delivery across North America for youth who engage in NSSI.